Case Report and Systematic Review: Sarcomatoid Parathyroid Carcinoma—A Rare, Highly Malignant Subtype - Yu, Yongchao; Wang, Yue; Wu, Qingcheng; Zhao, Xuzi; Liu, Deshun; Zhao, Yongfu; Li, Yuguo; Wang, Guangzhi; Xu, Jingchao; Chen, Junzhu; Zhang, Ning; Tian, Xiaofeng (Frontiers in Endocrinology, 2021)
Background. Parathyroid carcinoma (PC) is a rare malignancy, which incidence is less than 1/1000000 per year. Sarcomatoid parathyroid carcinoma (SaPC) is an extremely peculiar subtype, only 3 cases have been reported internationally. It consists of both malignant epithelial components and sarcomatoid components (mesenchymal origin) simultaneously. This “confusing” cancer exhibits higher invasiveness, and traditional surgery does not appear to achieve the expectation, which differs significantly from that of general PC. Objective. To characterize the clinicopathologic features of SaPC and explore similarities and differences between SaPC and general PC. Materials and methods. We collected clinical data of SaPC cases from our center and literature. The SaPC case in our center was presented. To better understand the characteristics of SaPC, we also reviewed clinical information in general PC cases from our center and literature within the last 5 years, and a systematic review was performed for further comparison. Results. A 60-year-old woman was admitted for a neck mass and hoarseness. After the surgery she was confirmed as SaPC and ultimately developed local recurrence at 3 months. Together with the reported cases from literature, 4 cases of SaPC (3 cases from literature) and 203 cases of general PC (200 cases from literature) were reviewed. Both tumors showed obvious abnormalities in parathormone (PTH) level and gland size. Compared to general PC, SaPC has a later age of onset (60.50±7.42 vs 51.50±8.29), relatively low levels of PTH (110.28±59.32 vs 1156.07±858.18) and a larger tumor size (6.00±1.63 vs 3.14±0.70). For SaPC, all 4 cases were initially misdiagnosed as thyroid tumors (4/4). Spindle cell areas or transitional zones were common pathological features in SaPC cases (3/4). Conclusion. SaPC is a very rare pathologic subtype of PC and appears to be much more easily misdiagnosed as thyroid tumors. Spindle cell areas or transitional zones are highly possible to be pathological features in its sarcomatoid components. Despite many similarities, there are some differences between SaPC and general PC—SaPC does not show the obvious endocrine feature but stronger aggressiveness. Surgical treatment of SaPC does relieve life-threatening symptoms and improve quality of life even the recurrence occurred in the short term.